DAMPAK PENGARUH BURSA SAHAM GLOBAL, HARGA EMAS DUNIA DAN VARIABEL MAKROEKONOMI TERHADAP INDEKS HARGA SAHAM GABUNGAN PERIODE 2009-2018. - NURISMA SARI, DEBY; PURWOHANDOKO, (Jurnal Ilmu Manajemen (JIM), 2019)
This purpose of this research to analyze the influence of the Dow Jones Industrial Average (DJIA) index, Nikkei 225 index, world gold prices, net exports, inflation, exchange rate and SBI interest rates on the Composite Stock Price Index period 2009-2018. The dependent variable in this research is the Composite Stock Price Index (CSPI), while the independent variables include the Dow Jones Industrial Average (DJIA) index, Nikkei 225 index, world gold prices, net export, inflation, exchange rate and SBI interest rates. This study uses the ratio of changes every month to obtain the sample number is 120. This research use multiple linear regression analysis method. The proceeds of this research that Nikkei 225 index, world gold price, net exports,, and inflation have no effect to CSPI. Meanwhile Dow Jones Industrial Average (DJIA) has a significant positive effect on the CSPI, exchange rate and SBI interest rates have a significant negative effect on the CSPI. Then all independent variables are simultaneously have effect Composite Stock Price Index. The Adjusted R square value are 0.510 which means that the movement of Composite Stock Price Index influenced 51% by the variables on this study and 49% is described by other variables outside model this research. Keywords: composite stock price index; global index; gold price; macroeconomics